2002
DOI: 10.1046/j.1440-1738.2002.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and Sr–Nd–Pb isotopic investigation of Triassic granitoids and basement rocks in the northern Gyeongsang Basin, Korea: Implications for the young basement in the East Asian continental margin

Abstract: We present chemical and Sr–Nd–Pb isotopic compositions of three Triassic (226–241 Ma) calc‐alkaline granitoids (the Yeongdeok granite, Yeonghae diorite and Cheongsong granodiorite) and basement rocks in the northern Gyeongsang basin, south‐eastern Korea. These plutons exhibit typical geochemical characteristics of I‐type granitoids generated in a continental magmatic arc. The Yeongdeok and Yeonghae plutons have similar initial Sr, Nd and Pb isotope ratios (87Sr/86Srinitial = 0.7041 ~ 0.7050, ɛNd(t) = 2.3 ~ 4.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 44 publications
2
55
1
1
Order By: Relevance
“…It had been reported that the age of the Satkatbong pluton is 70~75 Ma through the fission track method, then reported as 118.4±4.0 Ma with K-Ar chronological analysis (Kim et al, 1999). On the other hand, the age for the Satkatbong pluton when described as the Yeonghae diorite was reported from 178.0±4.3 Ma by the K-Ar method (Kim, 1997) to 238±14 Ma by Nd-Sm isochron (Cheong et al, 2002), which is actually included in the Jurassic. Actual field geology of the Satkatbong pluton, however, shows that it resembles the Yeonghae diorite rather than the Jangsari granite, so the age representing the Jurassic is preferred.…”
Section: Age Of the Satkatbong Plutonmentioning
confidence: 99%
See 3 more Smart Citations
“…It had been reported that the age of the Satkatbong pluton is 70~75 Ma through the fission track method, then reported as 118.4±4.0 Ma with K-Ar chronological analysis (Kim et al, 1999). On the other hand, the age for the Satkatbong pluton when described as the Yeonghae diorite was reported from 178.0±4.3 Ma by the K-Ar method (Kim, 1997) to 238±14 Ma by Nd-Sm isochron (Cheong et al, 2002), which is actually included in the Jurassic. Actual field geology of the Satkatbong pluton, however, shows that it resembles the Yeonghae diorite rather than the Jangsari granite, so the age representing the Jurassic is preferred.…”
Section: Age Of the Satkatbong Plutonmentioning
confidence: 99%
“…1. Simplified geological map of the study area in Yeongdeok (modified after Hatae, 1937;Kim 1968;Chang, 1990;Cheong et al, 2002). Sampling site is presented in appendix.…”
Section: Occurrencementioning
confidence: 99%
See 2 more Smart Citations
“…연구지역에서는 연대측정 (Kim et al, 1999, Yi et al, 2012a, 지화학 분석 (Cho and Kwon, 1994;Cheong et al, 2002), 화강암의 분류 (Jwa et al, 2005), 흑운모의 진화경로 (Lee and Kim, 1990) 및 심성암체내 알칼리장석의 상전이 루어져 있으며, 연구지역은 영덕 화강암이라 불리는 화강암질암류이다 (Fig. 1) (Kim, 1971;Won et al, 1978)으로 의견이 분분하 였으나 이후 절대연령 측정 연구 (Cheong et al, 2002;Sagong et al, 2005, Yi et al, 2012a (Fig.…”
Section: 에 이르는 다양한 분야의 연구들이 수행되었다 영덕화강암은 경상분지의 북동부 해안선으로부터unclassified